Prevalence of Fibromyalgia in Iraqi Patients with Ischemic Heart Disease - Al-Bidri, Khudhir M.; Gorial, Faiq I.; Al-Rawi, Ziad S.; Yousif, Muslim A. (Journal of the Faculty of Medicine Baghdad, 2009)
Background: Fibromyalgia has been associated with physical and emotional trauma including invasive medical procedures. Both Fibromyalgia and ischemic heart disease have been linked with depression. The aim of the study is to assess the prevalence of fibromyalgia syndrome in patients with ischemic heart disease.Patients and Methods: A cross-sectional comparative study was done in the Iraqi Center for Heart Disease. One hundred patients, angiographically proved to have ischemic heart disease, were subjected to rheumatologic examination by another physician, and compared to hundred healthy individuals as a control group. Diagnosis of fibromyalgia was based on 1990 American College of Rheumatology Classification criteria for the diagnosis of fibromyalgia.Results: Eighteen (18%) patients with ischemic heart disease fulfilled the American College of Rheumatology criteria for fibromyalgia syndrome in comparison to only 6(6%) of the controls, and this difference is statistically significant (P-value = 0.009).There were statistical significant effects of gender, age, and number of coronary vessels on the prevalence of fibromyalgia syndrome. Conclusion: fibromyalgia occurs with high frequency (18%) in patients with ischemic heart disease.